Sonographic Pattern of Ocular Pathologies at Murtala Muhammad Specialist Hospital, Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Ultrasonography is a non-invasive, inexpensive and safe imaging modality for diagnosing ocular pathologies, which aids in diagnostic accuracy and patient care.Aim:The aim of the study is to determine the pattern of ocular pathologies using ultrasonography at Murtala Muhammad Specialist Hospital.Settings and Design:This is a retrospective and descriptive study on sonographic pattern of various ocular pathologies.Materials and Methods:A total of 290 patients with various ocular pathologies were retrospectively reviewed within the study period from January 2017 to July 2018, in whom fundal examination was not possible due to media opacities and/or intraocular haemorrhage.Statistical Analysis Used:The data generated were analysed using SPSS version 21.0 program (SPSS Inc., Illinois, USA).Results:Cataracts were the most common ocular pathology detected sonographically, accounting for (45.5%) followed by vitreous haemorrhage (14.8%) and then retinal detachment (7.9%). Cataract has the highest frequency in all age groups with the highest frequency (34.1%) in 61–75 years of age group, while retinal (39.1%) and vitreous detachments (66.7%) have the highest frequency in the 16–30 and 61–75 years of age groups, respectively. The retinal detachment (52.2%) was more frequent in females, while cataract (54.5%) and vitreous haemorrhage (74.4%) were more frequent in males. Retinoblastoma (60%) and endophthalmitis (100%) were seen more on the right side, but the retinal detachment, cataract and vitreous haemorrhage were seen more on the left side.Conclusion:Ultrasonography is an important tool in the diagnosis of various ocular pathologies.